PENINGKATAN KETERAMPILAN BERBICARA BAHASA MANDARIN DENGAN MENGGUNAKAN METODE DRILL PADA SISWA KELAS V SD ZION GKKA-UP MAKASSAR - Bongga, Risda; Dalle, Ambo; Nasharuddin Noni, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the speaking skills of fifth-grade students at SD Zion GKKA-UP Makassar through the application of the drill method. The participants of this study consisted of 30 students. The research employed a Classroom Action Research (CAR) design conducted in two cycles. Qualitative data were collected through observation sheets of teacher and student activities, while quantitative data were obtained from speaking skill test results in Cycle I and Cycle II. The findings showed that the average speaking score in Cycle I was 64.17, categorized as low, and increased to 74.67 in Cycle II, categorized as good. These results indicate that the implementation of the drill method in Mandarin language learning is effective in improving the speaking skills of fifth-grade students at SD Zion GKKA-UP Makassar.